A novel theranostic nano-platform (PB@FePt–HA-g-PEG) for tumor chemodynamic–photothermal co-therapy and triple-modal imaging (MR/CT/PI) diagnosis. Issue 24 (27th May 2020) - Hu, Zunfu; Wang, Shan; Dai, Zhichao; Zhang, Hongxiu; Zheng, Xiuwen
Abstract : We have successfully designed and fabricated a nano-agent (PB@FePt–HA- g -PEG NCs) to serve as a versatile nano-platform with both highly specific targeting ability for chemodynamic–photothermal co-therapy and triple-modal imaging capability. Abstract : The construction of multi-functional oncotherapy nano-platforms combining diagnosis and therapy remains a tough challenge. Prussian blue nano-cubes with optimized particle size were applied as photothermal agents and loaded with FePt NPs, effective ferroptosis agents, on the surface via an in situ reduction strategy. To attain the goal of precise medicine, hyaluronic acid was wrapped around the surface of the nanocomposites (PB@FePt NCs) for highly specific recognition of tumor cells. Finally, we successfully designed and fabricated a nano-agent (PB@FePt–HA- g -PEG NCs) to serve as a versatile nano-platform with both highly specific targeting ability for chemodynamic–photothermal co-therapy and triple-modal imaging (magnetic resonance/computed tomography/photothermal imaging) capability. Via intravenous injection, the as-constructed oncotherapy nano-platform could effectively ablate 4T1 tumor xenografts with excellent biocompatibility for chemodynamic–photothermal co-therapy. In this study we conducted a reasonable exploration to design multi-functional oncotherapy nano-platforms combining multiplexed imaging diagnosis and high therapeutic performance, which provides an innovative paradigm for precision cancer treatment.